PENGEMBANGAN DESAIN RUMAH TUMBUH STUDI KASUS PERUMNAS WONOREJO KARANGANYAR - Silfia Mona Aryani; Iik Endang Siti Wahyuningsih; Mulyadi Mulyadi; Andi Setiawan; Soepono Sasongko (LINTAS RUANG: Jurnal Pengetahuan dan Perancangan Desain Interior, 2018)
This article explains the result of a community service program entitiled assistance on Rumah Inti Tumbuh (RIT) Design Transformation of Wonorejo National Housing Karanganyar. The program was conducted in two steps. The first one was a counseling session for explaining the RIT concept and how the right development is in order to meet the criterion of the healthy and comfort house. This session is purposed for encouraging the owner of how important of right house development without reducingits quality. The second step was the assistance process in developing the RIT. This process considers the previous research conclusion in the transformation preference that are room programming addition, room replacement and room widening. This program focused on the undeveloped units that are planned to be transformed. The assistance will recommend the design that might meet the every family need without compromising the health and comfort aspect. In the end, this community service program is hoped to reduce the bad impact of the development as it is provided by the guidance from the competent experts.